Antigenic Competition - Shnawa, Ibrahim Mohamed Saeed (Vaccines and Vaccine Interference, 2023)
It has been observed that in a dimicrobic mucosal urinary tract infection. The specific antibody titre of E. coli was higher than that of P. aeruginosa. The interpretation was based on antigenic competition. Hence a case of UTI with combined gram negative infection were chosen and diagnosed as E. coli and P. aeruginosa (Identified by classical tests and API 20E system). Balanced and unbalanced heat killed E. coli and P. aeruginosa antigens in different combination proportions were made and used for specific immune priming of rabbits. Monotypic heat killed antigens were made and used for priming rabbits separately standard tube agglutination and ELISA IL-4 were used to match humoral and cellular arms respectively in the state of secondary immune responses. The specific antibody mean titres in combinations was reduced as compared to mean titres of monotypic sera which is an indication for antigenic competition. It was reciprocal intermolecular type (T cell dependent). IL-4 determinations were increased as compared monotypic and control in the sera react against unbalanced combinations. Such increase indicate its role in antigenic competition. Thus, the E. coli, P. aeruginosa antigenic competition is a reciprocal, humoral and cellular and intermolecular type. The role of IL-4 in antigenic competition is being reported for the first time.